Characterization of the oriC region of Mycobacterium smegmatis. - Qin, M H (1997)
A 3.5-kb DNA fragment containing the dnaA region of Mycobacterium smegmatis has been hypothesized to be the chromosomal origin of replication or oriC (M. Rajagopalan et al., J. Bacteriol. 177:6527-6535, 1995). This region included the rpmH gene, the dnaA gene, and a major portion of the dnaN gene as well as the rpmH-dnaA and dnaA-dnaN intergenic regions. Deletion analyses of this region revealed that a 531-bp DNA fragment from the dnaA-dnaN intergenic region was sufficient to exhibit oriC activity, while a 495-bp fragment from the same region failed to exhibit oriC activity. The oriC activities of plasmids containing the 531-bp sequence was less than the activities of those containing the entire dnaA region, suggesting that the regions flanking the 531-bp sequence stimulated oriC activity. The 531-bp region contained several putative nine-nucleotide DnaA-protein recognition sequences [TT(G/C)TCCACA] and a single 11-nucleotide AT-rich cluster. Replacement of adenine with guanine at position 9 in five of the putative DnaA boxes decreased oriC activity. Mutations at other positions in two of the DnaA boxes also decreased oriC activity. Deletion of the 11-nucleotide AT-rich cluster completely abolished oriC activity. These data indicate that the designated DnaA boxes and the AT-rich cluster of the M. smegmatis dnaA-dnaN intergenic region are essential for oriC activity. We suggest that M. smegmatis oriC replication could involve interactions of the DnaA protein with the putative DnaA boxes as well as with the AT-rich cluster.